A cyber forensics needs analysis survey: Revisiting the domain's needs a decade later. Issue 57 (March 2016) - Harichandran, Vikram S.; Breitinger, Frank; Baggili, Ibrahim; Marrington, Andrew
Abstract: The number of successful cyber attacks continues to increase, threatening financial and personal security worldwide. Cyber/digital forensics is undergoing a paradigm shift in which evidence is frequently massive in size, demands live acquisition, and may be insufficient to convict a criminal residing in another legal jurisdiction. This paper presents the findings of the first broad needs analysis survey in cyber forensics in nearly a decade, aimed at obtaining an updated consensus of professional attitudes in order to optimize resource allocation and to prioritize problems and possible solutions more efficiently. Results from the 99 respondents gave compelling testimony that the following will be necessary in the future: (1) better education/training/certification (opportunities, standardization, and skill-sets); (2) support for cloud and mobile forensics; (3) backing for and improvement of open-source tools (4) research on encryption, malware, and trail obfuscation; (5) revised laws (specific, up-to-date, and which protect user privacy); (6) better communication, especially between/with law enforcement (including establishing new frameworks to mitigate problematic communication); (7) more personnel and funding.